2001
DOI: 10.1191/096032701678227730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vepacide (Azadirachta indica) on asp artate and al anine aminotransferase profiles in a subchronic study with rats

Abstract: The aim of this study was to ascertain the long-term effects of Vepacide, a neem-based pesticide on biochemical profiles. Albino Wistar rats were treated orally with 80 (low), 160 (medium) and 320 mg/kg (high) doses of Vepacide in coconut oil for 90 days. Control rats received the same volume of the vehicle. Vepacide caused increase of aspartate and alanine aminotransferase in serum, kidney and lung, and these enzymes decreased in liver in both male and female rats when measured after 45 and 90 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 12 publications
5
84
3
Order By: Relevance
“…This submission is in agreement with earlier report by Ashafa et al [20]. According to these authors, the significant reduction in organ-to-body weight observed in rats administered with P. dioica aqueous extract was attributed predict possible toxicity to the liver [23]. Therefore, the reduction in ALP activity in the liver and kidney of rats following administration of aqueous extract of P. nitida seeds may in part be due to damage to the plasma membrane of the two organs leading to a compromise of membranal integrity.…”
Section: Discussionsupporting
confidence: 93%
“…This submission is in agreement with earlier report by Ashafa et al [20]. According to these authors, the significant reduction in organ-to-body weight observed in rats administered with P. dioica aqueous extract was attributed predict possible toxicity to the liver [23]. Therefore, the reduction in ALP activity in the liver and kidney of rats following administration of aqueous extract of P. nitida seeds may in part be due to damage to the plasma membrane of the two organs leading to a compromise of membranal integrity.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the observed increase in serum activity of these enzymes in the untreated constipated rats may be indicative of damage to the plasma membrane, leading to compromised membranal integrity and reduced concentration of hepatic glutathione. AST and ALT are biomarkers to known predict physiological state of the liver and are significant in amino acid metabolism (Rahman et al 2001). In this study, the increased serum activities of these enzymes as observed in the untreated constipated rats suggested possible damage to the hepatocytes arising from alteration in membrane permeability, which may consequently impact on the metabolism of amino acids in the liver (Anofi et al 2012).…”
Section: Toxicologymentioning
confidence: 69%
“…16,17 Available evidence show that damage to liver cells results in elevations of these enzymes in the serum and the measurement of enzyme activities is of clinical and toxicological significance in determining liver damage by toxicants or in diseased conditions. 18,19 The level of these enzymes in the blood is directly related to the extent of the tissue damage.…”
Section: Discussionmentioning
confidence: 99%